Dissecting the interactive effects of hypoxia and Kaposi's sarcoma-associated herpesvirus on microrna and mrna transcriptomes - Viollet, C (2015)
Kaposi's sarcoma-associated herpesvirus (KSHV) causes several tumours and hyperproliferative disorders. Hypoxia plays an important role in KSHV lifecycle, as hypoxia-inducible factors (HIFs) are involved in the latent/lytic switch and affect other KSHV genes, and as KSHV infection can in turn enhance cellular levels of HIFs. Two KSHV-associated tumours tend to develop in settings of relative hypoxia; Kaposi's sarcoma (KS) often occurs in the lower extremities and primary effusion lymphoma (PEL) exists in pleural effusions. A better knowledge of the pathways that regulate KSHV infection in hypoxia is therefore essential for an improved understanding of viral infection and pathogenesis. MicroRNAs (miRNAs) have been shown to play important roles in regulating the expression of genes in oncogenesis, and herpesviruses, including KSHV, encode for miRNAs. This thesis describes a multidisciplinary approach toward understanding the mechanisms behind the hypoxia-regulated miRNA-mRNA networks in the context of KSHV infection. The question of miRNA and mRNA regulation through hypoxia, KSHV or both is addressed in this thesis by deep sequencing and gene expression assays as well as various transfection and functional assays. In chronically infected cells compared to uninfected controls, it is demonstrated that the majority of cellular miRNAs whose expression is affected are substantially down-regulated. A third of this down-regulation can be attributed to a single genomic region, 14q32 cluster, where miRNAs are lowly expressed in infected cells. In hypoxia, hsa-miR-210 is the only miRNA to be consistently up-regulated in the KSHVinfected cell lines subjected to deep sequencing in this study. Computational approaches additionally allowed for the investigation of mRNA targets. Inversely correlated miRNAmRNA target pairs were identified and distributed into canonical pathways and biological networks. Taken together, these results suggest that miRNAs affected by hypoxic stress and/or viral infection are implicated in the pathogenesis of KSHV-related diseases. It is expected that the outcomes of these studies will change our understanding of how KSHV uses the host RNA silencing machinery to its advantage and how this intersects with the use of the cell's response to hypoxia.